Association of ultra-processed food-related metabolites with selected biochemical markers in the UK Biobank - Anthony Kityo; Byeonggeun Choi; Jung-Eun Lee; Chulho Kim; Sang-Ah Lee (Nutrition Journal)
Abstract Background Ultra-processed food (UPF) intake is positively associated with multiple adverse health outcomes. However, the underlying biological mechanisms remain unclear. Serum metabolites may elucidate these mechanisms. We investigated serum metabolites correlated with UPF and un/minimally processed food (UNPF) intake and evaluated their association with selected biochemical markers. Methods Cross-sectional study within the UK biobank, including a total of 72,817 participants with 24-hour recall dietary data and 134 nuclear magnetic resonance metabolites. UPF and UNPF intakes were evaluated using the NOVA classification, and related metabolites were identified using elastic net penalized regression. A UPF metabolomic signature was computed as a weighted sum of UPF-related metabolites, using elastic net coefficients as weights. Associations between UPF and UNPF-related metabolites, and serum C-reactive protein (CRP), insulin-like growth factor-1(IGF-1), sex hormone-binding globulin (SHBG), and testosterone were examined using multiple quantile regression. Results Elastic net model identified 17 and 15 metabolites uniquely related to UPF and UNPF intake, respectively. Acetoacetate, acetone, high-density lipoprotein (HDL) diameter, docosahexaenoic acid, linoleic acid, ω-3 fatty acids (FA), total lipids in large HDL cholesterol, and valine levels were decreased, but free cholesterol in extremely small very low-density lipoproteins (LDL), glutamine, glycine, glycoprotein acetyls, lactate, saturated FA, sphingomyelins, triglycerides in large LDL, and triglycerides in medium HDL levels were increased with high UPF intake. Opposite relationships were observed for UNPF intake. Heterogeneous associations were observed between UPF-related metabolites and CRP, IGF-1, SHBG, and testosterone levels. A UPF metabolomic signature was positively associated with CRP (regression coefficient per standard deviation, 1.45, 95% confidence interval, 1.385, 1.515) and negatively associated with IGF-1 (-3.16, -4.493, -1.827) and SHBG (-13.878, -15.291, -12.465). Conclusion A UPF metabolomic profile, including VLDL free cholesterol, saturated FA, triglycerides, glutamine, glycine, and glycoprotein acetyl was associated with inflammatory, insulin signalling, and reproductive biomarkers. This metabolomic profile should be explored as a potential mediators of UPF-disease associations, and as an objective marker of UPF intake.